Geno- and phenotypic characteristics and clinical outcomes of CACNA1C gene mutation associated Timothy syndrome, “cardiac only” Timothy syndrome and isolated long QT syndrome 8: A systematic review - Borbás, János; Vámos, Máté; Hategan, Lidia; Hanák, Lilla; Farkas, Nelli; Szakács, Zsolt; Csupor, Dezső; Tél, Bálint; Kupó, Péter; Csányi, Beáta; Nagy, Viktória; Komócsi, András; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Mutations in the CACNA1C gene - encoding the major Ca2+ channel of the heart - may exhibit a variety of clinical manifestations. This includes typical or atypical Timothy syndrome (TS) which are associated with multiple organ manifestations, and cardiac involvement in form of malignant arrhythmias, QTc prolongation, or AV block. ‘Cardiac only’ Timothy syndrome (COTS) shows no extracardiac manifestation, whereas some CACNA1C gene mutations are associated with QTc prolongation alone (long QT syndrome 8, LQT8). Methods: A systematic search of the literature reporting cases of CACNA1C gene mutation associated syndromes, including TS, COTS and LQT8 via major databases published from 2004 through 2019 was performed. Detailed patient-level phenotypic and genotypic characteristics, as well as long-term outcome measures were collected and compared between prespecified patient groups, defined both on phenotype and genotype. Results: A total of 59 TS, 6 COTS, and 20 LQT8 index cases were identified. Apart of syndactyly or baldness, there were no major differences regarding clinical manifestations or outcome measures between TS subtypes, either defining TS subtypes on the genotype or based on the phenotype. Both subtypes were characterized by an extreme degree of QTc prolongation (median ≥600 ms) which were reflected in high major adverse cardiac event rate. On the other hand, there were marked differences between TS, COTS and LQT8. Timothy syndrome was characterized by a much earlier disease onset, much more pronounced QTc prolongation and much higher mortality rate than COTS or LQT8. Similar differences were observed comparing CACNA1C exon 8/8A vs. non-exon 8/8A mutation carriers. TS showed a high degree of genetic homogeneity, as the p.Gly406Arg mutation either 2 in exon 8 or exon 8A alone was responsible for 70% of the cases. Conclusions: Clinical phenotypes associated with mutations in the CACNA1C gene show important clinical differences. Timothy syndrome is associated with the most severe clinical phenotype and with the highest risk of morbidity and mortality. However, distinguishing TS subtypes, in any form, are not supported by our data. Clinical Trial Registration: Prospero - CRD42020184737.